Nucleic acid and protein methylation modification in renal diseases - Jin Juan; Liu Xue-mei; Shao Wei; Meng Xiao-ming (Acta Pharmacologica Sinica, 2024)
Although great efforts have been made to elucidate the pathological mechanisms of renal diseases and potential prevention and treatment targets that would allow us to retard kidney disease progression, we still lack specific and effective management methods. Epigenetic mechanisms are able to alter gene expression without requiring DNA mutations. Accumulating evidence suggests the critical roles of epigenetic events and processes in a variety of renal diseases, involving functionally relevant alterations in DNA methylation, histone methylation, RNA methylation, and expression of various non-coding RNAs. In this review, we highlight recent advances in the impact of methylation events (especially RNA m6A methylation, DNA methylation, and histone methylation) on renal disease progression, and their impact on treatments of renal diseases. We believe that a better understanding of methylation modification changes in kidneys may contribute to the development of novel strategies for the prevention and management of renal diseases.